Croatia's Destination Branding Efforts Through The Game of Thrones Television Series - Aviantara, Jennifer; Widya Nugraha, A.A. Bagus Surya; Kumala Dewi, Putu Ratih (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 4 No 2 (2024): JURNAL DIKSHI, 2024)
Tourism has key role in enhancing the image of Croatia. It makes the government of Croatia concerns of Croatia’s tourism sector, beside of tourism enhances Croatia’s image, it also contributes to Croatia’s economy while in the middle of economic crisis. The utilization of television serial Game of Thrones which is a media from popular culture that is utilized by Croatia to enhance their destination branding. The utilization of the television serial Game of Thrones by Croatia capable in increasing the number of visits to areas that is used as shooting locations for Game of Thrones. This research studies the effort of Croatia to strengthen Croatia’s destination branding capitalize on the popularity of Game of Thrones. By using the method of descriptive qualitative, the concept used in this research to analyze is soft power, screen tourism, and destination branding. The result of this research shows that Croatia utilizes Game of Thrones to develop new tourism product which is screen tourism to reach a wider market. In developing screen tourism, Croatia creates new tourism attractions and shares information associated with Game of Thrones via tourism exhibition in other countries, and through various online medias such as official social media, official website, and news articles. Eventually, the effort of Croatia to utilize the television serial Game of Thrones is effective in achieving Croatia’s concern, that is Croatia wants to be known positively in a wider circle.